Exploring Quillbot’s Role in Enhancing Integrated Language Assessment in EFL Classrooms - Cheolmin, Park; Firdaus, Masagus; Rafli, Muhammad (JET ADI BUANA, 2025)
In the digital era of language education, he rapid integration of Artificial Intelligence (AI) into language education has opened new avenues for teaching and assessment, yet studies examining the pedagogical role of such tools in integrated language assessment remain limited. This article addresses this gap by exploring how QuillBot, an AI-powered paraphrasing and grammar-checking tool, can enhance English as a Foreign Language (EFL) assessment, especially in tasks requiring a synthesis of reading, writing, grammar, and vocabulary skills. Unlike traditional tools, QuillBot offers a unique interface that promotes process-based writing and reflective revisions. Employing a library-based research method, the study reviews recent scholarly work (2020–2025) to evaluate the educational affordances and limitations of using QuillBot in EFL contexts. The findings suggest that while QuillBot facilitates integrated skill development, its effective use depends on pedagogical guidance and ethical considerations. This paper provides practical insights for educators seeking to implement AI meaningfully in language learning and assessment